2007
DOI: 10.1063/1.2747677
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the critical Shields number for particle erosion in laminar flow

Abstract: International audienceWe present reproducible experimental measurements for the onset of grain motion in laminar flow and find a constant critical Shields number for particle erosion, i.e., c = 0.12± 0.03, over a large range of small particle Reynolds number: 1.5 10 −5 Re p 0.76. Comparison with previous studies found in the literature is provided

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 11 publications
12
127
3
Order By: Relevance
“…We remark that the critical Shields numbers detected in our study and also in that by Charru et al 20 are considerably lower than those around 0.12 provided by Ouriemi et al, 17 Charru et al 20 and Derksen 19 for the onset of particle motion in irregularly arranged granular beds. In view of our results, this can be understood due to the strong dependence of the critical Shields number on the burial degree as well as on the angle between flow and substrate orientation.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…We remark that the critical Shields numbers detected in our study and also in that by Charru et al 20 are considerably lower than those around 0.12 provided by Ouriemi et al, 17 Charru et al 20 and Derksen 19 for the onset of particle motion in irregularly arranged granular beds. In view of our results, this can be understood due to the strong dependence of the critical Shields number on the burial degree as well as on the angle between flow and substrate orientation.…”
Section: Discussioncontrasting
confidence: 50%
“…Fluids 24, 093302 (2012) this phenomenon as bed armouring, which yields an increase of the threshold for particle motion. 16 Independent from the particle Reynolds number, Ouriemi et al 17 observed in their experimental study a constant critical Shields number for incipient motion of about 0.12 in laminar flow at about the same value as Charru et al 16 for a saturated compact bed. Studying a single particle on an irregularly arranged bed of identical particles, Charru et al observed an influence of the local substrate geometry on the onset of particle motion and the traveling trajectory.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…But this number that is specifically defined for fully turbulent flow regimes is no more relevant for a laminar jet as will be studied here after. Several previous studies have focused on the onset of particle motion in laminar flow condition with irregular granular substrates [16,18,29,34] or also regular ones [2]. Based on their results considering a planar impinging liquid jet, Badr et al [5] have concluded that the initiation of grain movement can be satisfactorily predicted by a critical inertial Shields number around 1 for particle Reynolds numbers ranging from 3 to 80, by assuming a simplified expression for the inertial flow stress derived from both laminar and turbulent free plane jet models [41] which therefore seem to be valid for a jet impinging on a granular sample.…”
Section: Introductionmentioning
confidence: 99%